Return on Investment in Research, Development and Innovation: Model for the University. - Ismodes C., Eduardo (2001)
this article describes the research, development and innovation (I + D + I), in Peru, from conceptual approaches and information documents, considering proposed solutions in order to identify a system that links people and institutions.